Damage survey and seismic vulnerability assessment of unreinforced masonry structures in low-intensity Ambasa earthquake of northeast India. (October 2022) - Debnath, Pranoy; Halder, Lipika; Chandra Dutta, Sekhar
Abstract: Unreinforced masonry (URM) buildings in many developing countries are susceptible to severe damage during earthquakes as these are designed and constructed without considering the earthquake risk of that region. Many low-rise URM buildings in Tripura, a northeast state of India, have suffered substantial damage during the recent low-intensity Ambasa earthquake (Mw 5.7). In this context, a damage survey was conducted at first to assess the cause behind the damaged URM buildings. Thereafter, a publicly funded three-storied URM building in Kumarghat, Tripura, has been chosen as a typical representative case for the vulnerability assessment. The Equivalent Frame Modelling approach has been used to model the building in SAP2000 with three different sets of material properties. The Incremental Dynamic Analysis is performed considering seven ground motions to obtain the damage measures for fragility analysis. The visual observations and numerical results match well for the damaged building. In fact, the modelling and analysis technique seems to predict the reasonably accurate damage scenario within a limited computational effect. This opened up a possibility for assessing seismic of masonry buildings on a regular basis which was otherwise a challenge. It has been found that the use of poor quality materials is the primary reason behind the damage to the buildings in such earthquakes. The derived fragility curves also show that with the deterioration of material quality, the probability of suffering moderate to extensive damage increased significantly at the PGA level of 0.052 g that was recorded during the earthquake. Hence, this paper may help the practising engineer to understand several cruxes of vulnerability involved in the design and construction of structures. Further, the method summarized in this study may be extended for the vulnerability assessment of all the building typologies of the earthquake-prone areas of developing countries.